Gender similarities in high school mathematics: affective and cognitive aspects - Negasi Hagos Tekola; Dawit Asrat Getahun; Hailu Hagos (Bahir Dar Journal of Education)
The study investigated gender similarities in perceived teacher affective support, mathematics self-efficacy, and mathematics achievement by using quantitative research design. Data were collected by self-report questionnaire and achievement test from 727 (416 females & 311 males) grade 9 students, with average age of 15 years, randomly selected from three government general secondary schools in Aksum. Data gathering tools had acceptable reliability coefficients; 0.80 for teacher affective support scale and 0.93 for mathematics self-efficacy scale. Descriptive statistics and independent samples t-test were used to analyze the data. The findings revealed that there were gender similarities in teacher affective support and mathematics achievement while girls found to be more self-efficacious towards mathematics. The findings can be practically used to realize successful high school mathematics teaching-learning by selecting student outcomes, designing teacher and school manager training programs, and developing curricular materials in line with the findings. Mathematics teachers in particular can practically use the findings to enhance good insights in students, successfully support their students, and can work on improving mathematics self-efficacy and thereby enhance learning and achievement in mathematics for all students. Theoretically, the study confirmed Hyde’s (2005) gender similarity hypothesis and this investigation in the Ethiopian high school mathematics context contributes to the contested research in gender and mathematics which could contribute to the theories in educational psychology. Further implications and directions for future study are forwarded.